ANALISIS PENDAPATAN, PERSEPSI, DAN MINAT PETANI DALAM BERUSAHATANI UBI KAYU DI KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR - Anggelia Permata Sari; Raden Hanung Ismono; Rabiatul Adawiyah (Lampung University, 2020)
The objectives of this study are to find out the profit, the farmers’ perception, the farmers’ interest of industrial cassava farmers, and to analyze factors affecting of the farmers’ interest for the industrial cassava. The locations of this study are chosen purposively in Sukadana and Rajabasa Batanghari Villages, Sukadana District, East Lampung Regency. The number of respondents were 64 farmers selected using simple random sampling method. The data were collected in September - October 2018. The profit is analyzed descriptively, the farmers’ perception is analyzed using the Likert Scale, and the factors affecting farmers’ interest are analyzed using binary logistic regression. The results of this study showed that the profit was IDR10,355,938.25 per hectare. The farmers’ perception of the industrial cassava farming was easy because of its the easiness of cultivation, the reliability of market, the availability of the agricultural extension, and the fulfillment for the farmers’ needs. The farmers’ interest in cassava farming was low. The factors affecting the farmers’ interest in cassava farming were the planting area and the price of the cassava.Key words: agriculture, cassava farmers, interests, perception